2016
DOI: 10.14260/jemds/2016/543
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Programmed Deep Breathing Exercises on Reducing the Level of Fatigue During External Radiation Therapy

Abstract: CONTEXTCancer related fatigue is the most common symptom described by cancer patients receiving radiation therapy. AIMTo assess the effectiveness of programmed deep breathing exercises on reducing the level of fatigue during external radiation therapy in cancer patients in some selected hospitals of Guwahati, Assam. SETTINGS AND DESIGNExperimental, pretest-post-test control group designed to select 60 cancer patients in Dr. B. Barooah Cancer Institute and North East Cancer Hospital and Research Institute, Guwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Therefore, the researchers concluded that the four times RBE significantly alleviates fatigue in patients with gynaecological cancer undergoing chemotherapy. Devi [25] also reported that programmed deep breathing exercises reduced the level of fatigue in patients with cancer during external radiation therapy. This finding is also similar to that in the research conducted by Kim SD and Kim HS [28] on the effects of RBE on fatigue in patients with leukaemia undergoing hematopoietic transplant, although the intervention was conducted for 6 weeks once a day for 30 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the researchers concluded that the four times RBE significantly alleviates fatigue in patients with gynaecological cancer undergoing chemotherapy. Devi [25] also reported that programmed deep breathing exercises reduced the level of fatigue in patients with cancer during external radiation therapy. This finding is also similar to that in the research conducted by Kim SD and Kim HS [28] on the effects of RBE on fatigue in patients with leukaemia undergoing hematopoietic transplant, although the intervention was conducted for 6 weeks once a day for 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…RBE is a conscious act to deeply and slowly regulate breathing to achieve relaxation [22,23] and consists of physical exercise combined with breathing exercise that can be independently performed by patients [24,25]. RBE affects the stress response system and relaxes the mind and body when energy consumption is reduced or none is expended at all [26].…”
Section: Introductionmentioning
confidence: 99%
“…There are studies showing that breathing exercises are effective in reducing fatigue in cancer patients [14,25,34,47,48]. Devi et al determined that deep breathing exercises reduced fatigue in patients receiving radiotherapy [42].…”
Section: Discussionmentioning
confidence: 99%
“…Both pranayama and deep breathing exercises are easy to learn. They can be used individually or as a group at anytime and anywhere and are exercises that can be done without creating stress on the person and without consuming too much energy [14,42,47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation